Effect of heavy metal on the karyotype of Channa punctatus - N P, Ancy Mathew; Jahageerdar, Srinivas (Indian Journal of Fisheries, 2011)
An experiment was set up to assess the effect of lead on the karyotype ofChanna punctatus. The effects of lead in the form of lead nitrate was studiedfor 96, 120 and 144 hours at 0.012, 0.025 and 0.050 mg/1 of water. The modelnumber of chromosome was found to be 2n = 32 out of which 14 weremetacentric, 8 submetacentric, 6 telocentric and 4 acrocentric. The lead nitrateinduced structural chromosomal aberrations were breaks, fragments, dicentricand ring type chromosomes. Lead nitrate at a very low concentration of 0.012mg/1 and for just 96 hours of exposure can induce chromosomal aberrationsin fish.